Optimalisasi Kesehatan Masyarakat Melalui Pencegahan Mumps - Atzmardina, Zita; Christopher Amadeus Nicholas; Fathiyah Fathiyah; Tiffany Avelia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Community diagnosis is a strategic step that aims to identify fundamental problems in the community, determine problem priorities, and formulate appropriate solutions to overcome them. One of the identified health issues is a significant increase in cases of mumps (epidemic parotitis), an acute infectious disease caused by the mumps virus, a member of the Rubulavirus genus. This increase in cases was recorded in the Puskesmas work area from the beginning of the year to November 2024. This phenomenon raises concerns regarding the potential for widespread health problems at the community level. Therefore, this intervention activity was carried out with the hope of reducing the incidence of mumps in the Puskesmas work area.The methodology applied in this activity includes data collection through mini surveys, analysis of health determinants using the Blum Paradigm, determination of problem priorities through the Delphi method, and identification of root causes using a fishbone diagram. Based on the results of this analysis, the interventions implemented include counseling on mumps and preventive measures, as well as demonstrations of proper hand washing. The results of the intervention showed a significant increase in knowledge, where all participants (n=40, 100%) obtained a post-test score of ≥ 7, indicating a good understanding of the material presented. In the demonstration session, a number of participants were also able to demonstrate the steps for washing hands according to the correct procedure. From the results of the analysis, it was found that the increase in mumps cases in this area was closely related to community lifestyle factors. Therefore, this intervention is expected to not only increase community knowledge about mumps, but also encourage the implementation of clean and healthy living behaviors, especially in the practice of washing hands, as a preventive measure to reduce the number of transmissions and accelerate case handling.